2021
DOI: 10.1007/s10064-021-02537-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity survey for evaluating the undrained shear strength of soft Bangkok clay at some of the canal-side road investigation sites

Abstract: A resistivity-undrained shear strength equation was proposed in this work to investigate the relationship between the undrained shear strength and electrical resistivity of soft Bangkok clay. The field vane shear and screw driving sounding tests were used to evaluate the undrained shear strength of the soft Bangkok clay from 10 field investigations of the canal-side roads. Meanwhile, the electrical resistivity was collected by the low-cost nondestructive resistivity survey method. The relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…PLAXIS (American Bentley Systems, Inc., Exton, PA, USA) ennsylvania is the most reliable software for FEM modeling and solving problems in geotechnical work using two-dimensional (2D) FEM under plane strain conditions [38,39]. Moreover, several previous works revealed that the simulation results from PLAXIS software are aligned with the actual situation in complex ground conditions [40][41][42]. PLAXIS software is therefore suitable for simulating the geometry of the road embankment.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…PLAXIS (American Bentley Systems, Inc., Exton, PA, USA) ennsylvania is the most reliable software for FEM modeling and solving problems in geotechnical work using two-dimensional (2D) FEM under plane strain conditions [38,39]. Moreover, several previous works revealed that the simulation results from PLAXIS software are aligned with the actual situation in complex ground conditions [40][41][42]. PLAXIS software is therefore suitable for simulating the geometry of the road embankment.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The outcome suggested the two techniques can be used to investigate the stability of canal side roads. The electrical resistivity method estimated the shear strength of Bangkok clay as a primary appraisal for road construction (Chaiyaput et al, 2022).…”
mentioning
confidence: 99%